PUBLIC RELATIONS STRATEGIES OF THE INDONESIAN CHILDREN'S CANCER FOUNDATION IN INFLUENCING DONATION DECISIONS - Sari, Putri Nopita; Widiasanty, Gita (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Public Relations Strategy is a function of management's duties in carrying out communication, so the core objective is the communication goal to attract the public and companies to donate. There are many public relations strategies that can be done to get sympathy and attention from the public, one of which is by using social media. By using social media, companies can provide information and create posts that can attract the public and the company. Through this strategy, the Indonesian Child Cancer Foundation aims to touch the hearts of the community to donate. Carrying out this PR strategy can encourage decisions from the public and companies to make donations. The donor's decision to donate is the choice of each individual to choose where they will give their Public Relations funds to a company or voluntary foundation without expecting any feedback for them. This research aims to see the influence of Public Relations strategies on the decision to donate. This research uses quantitative data, namely by distributing questionnaires to donors of the Indonesian Child Cancer Foundation. This study had a population of 200 peoples and a sample of 67 peoples which was obtained from the Taro Yamane formula. This research uses simple regression analysis, validity test, reliability test, normality test and hypothesis test. The research results state that Public Relations strategies have a significant and positive influence on the decision to donate.